Translation and validation of the Portuguese version of the Keratoconus Outcomes Research Questionnaire (KORQ) - Pinto,Roberto Damian Pacheco (2021)
ABSTRACT Purpose: The purpose of this study is to translate and validate a Portuguese version of the Keratoconus Outcomes Research Questionnaire. The Keratoconus Outcomes Research Questionnaire is a psychometrically robust and valid instrument used to assess the impact of keratoconus on activity limitations and symptoms. Methods: We performed a translation, cross-cultural adaptation, and validation of the Portuguese version of the Keratoconus Outcomes Research Questionnaire. The initial translation of the English version to the Portuguese language was performed by two independent native speaker translators, followed by an interdisciplinary panel evaluation of the translated version. The Portuguese version was then back-translated into English by two independent native speakers, followed by evaluation and comparison with the original English version by the same interdisciplinary panel. For subsequent validation, the translated questionnaire was administered at two different times to a population of 30 subjects, and the results were compared in a concordance analysis. Results: The translation into Portuguese and back-translation were determined to be correct. Thirty participants were enrolled in the study (mean age, 29.23 ± 7.56 years). Nine questions (31%) had almost perfect agreement (questions 3, 4, 5, 8, 18, 22, 27, 28, and 29), 15 questions (51.7%) had substantial agreement (questions 1, 2, 6, 7, 9, 12, 14, 15, 16, 17, 20, 21, 23, 25, and 26), 4 questions (13.8%) had moderate agreement (questions 10, 11, 19, and 24) and 1 question (3.5%) had reasonable agreement (question 13). High-correlation coefficients were obtained when comparing results of the initial application and second application of this questionnaire to a sample of 30 individuals, which indicated excellent concordance with regard to results, repeatability, and reliability. Conclusions: This translated and validated questionnaire can be applied to a larger population with the intent to assess quality of life in keratoconus patients in the overall Brazilian population as well as in distinct regions of the country.